Lateral variations in the long‐term slip rate of the Chelungpu fault, Central Taiwan, from the analysis of deformed fluvial terraces. Issue 4 (25th April 2014) - Simoes, M.; Chen, Y.‐G.; Shinde, D. P.; Singhvi, A. K.
Abstract The Chelungpu fault ruptured during the September 1999 Mw 7.6 Chi‐Chi earthquake, in Central Taiwan. This event was characterized by coseismic displacements increasing along strike and updip, from south to north. Previous studies suggested that such lateral variations also existed in the long‐term fault slip rate, but this has not yet been clearly documented. To address this, we investigate deformed fluvial terraces along the Choushui and Tatu‐Wu rivers, in the southern and central segments of the thrust fault. Optical ages of ~13 ka to ~38 ka obtained for these terraces enable estimation of fault slip rates of 5.8 ± 2.0 and 10.3 ± 1.6/−3.0 mm/yr for the southern and central segments, respectively. We combine these findings with the fault slip rate determined by other authors for the northern segment. Statistical analysis of the data suggests lateral variations in the long‐term fault slip rate, with values increasing toward the north. This pattern in the slip rate, averaged over approximately tens of thousand years, is similar to that observed for coseismic displacements during the Chi‐Chi earthquake. The similarities in the deformation pattern observed for one earthquake or cumulated over several events suggest that the Chi‐Chi earthquake could be characteristic of the earthquakes breaking the Chelungpu fault, with respect to slip distribution. Our results also allow for discussing the plausible evolution of major rivers draining the foothills of central Taiwan over the last ~40–60 kyr.